Effect of Alkyl Alcohol on Viscosity of Silica-Based Chemical Gels for Decontamination of Radioactive Contaminations - Bon Yoon, Suk; Kim, Chang-Ki; Jung, Chong-Hun; Choi, Byung-Seon; Choi, Wang-Kyu; Lee, Kune-Woo; Moon, Jei-Kwon (Asian Journal of Chemistry, 2013)
Silica-based chemical gel for the decontamination of nuclear facilities was prepared using fumed silica as a viscosifier, a 0.5 M Ce (IV) solution dissolved in concentrated nitric acid as a chemical decontamination agent and tripropylene glycol butyl ether (TPGBE) as a coviscosifier. A new effective strategy for the preparation of the chemical gel was investigated by introducing the alkyl alcohols as organic solvents to effectively dissolve the coviscosifier. Using the mixture solution of the coviscosifier and alkyl alcohol was more effective in the control of viscosity than that of only coviscosifier in the gel. Here, alkyl alcohols play a key role as an effective dissolution solvent for the covicosifier in the preparation of the chemical gel, resulting in a reduction of the amount of covicosifier and gel time compared with that of the chemical gel prepared without alkyl alcohols. It was considered that the alkyl alcohols contributed to the effective dissolution of the coviscosifier as well as homogeneous mixing in the formation of the gel, while the coviscosifier in an aqueous media of the chemical decontaminant solution showed a lower solubility. The decontamination efficiency of the chemical gels prepared in this work using a multi-channel analyzer showed a high decontamination efficiency of over ca. 94 % and ca. 92 % for Co-60 and Cs-137 contaminated on the surface of stainless steel 304, respectively.